PENERAPAN SISTEM SURVEI KEPUASAN MAHASISWA DALAM MENINGKATKAN KINERJA PENGELOLA ADMINISTRASI AKADEMIK - Rani, Luisa Novita Ayu; Meilanda, Nurhidayati; Kamila, Zulfa; Yuliawan, Rahmat; Amaliyah, Amaliyah (Gapenas Publisher, 2024)
The use of information and communication technology has become important in the daily life of contemporary globalized and digital society. Utilization of technical systems for performance management and assessment is part of the application of High Tech in performance management. A company can better monitor employee performance and increase staff understanding of company goals by utilizing existing technology, including in educational institutions. However, improving the performance of a workforce requires assistance from the system for evaluation materials, namely student satisfaction surveys. The survey aims to collect feedback from students regarding the quality of academic services, so that it can be used to improve the quality of education at the university. The research method used in this research is a qualitative research method using in-depth interview research techniques to collect data and purposive sampling techniques to select research subjects. The results of this research show that the results of the student satisfaction survey and direct input from students will later be used as evaluation material to improve the performance of academic administration managers at the Faculty Y, University Z